2018
DOI: 10.1186/s13104-018-3975-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral response elicited against avian influenza virus infection following activation of toll-like receptor (TLR)7 signaling pathway is attributable to interleukin (IL)-1β production

Abstract: ObjectiveSingle stranded ribonucleic acid (ssRNA) binds to toll-like receptor (TLR)7 leading to recruitment of immune cells and production of pro-inflammatory cytokines, which has been shown in mammals. In chickens, ssRNA has been shown to elicit antiviral response against infectious bursal disease virus infection. The objectives of this study were to determine the pro-inflammatory mediators that are activated downstream of TLR7 signaling pathway in avian macrophages and their roles in antiviral response again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Although it has been shown that type 1 IFNs are induced following resiquimod treatment in other animal models [28], our previous work indicated the lack of production of type 1 IFNs and increased production of IL-1β following treatment of avian macrophage with resiquimod [15,27]. In agreement with the observations of these later studies, a lack of production of type IFNs have been shown in avian macrophages following stimulation of these cells with resiquimod [29].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although it has been shown that type 1 IFNs are induced following resiquimod treatment in other animal models [28], our previous work indicated the lack of production of type 1 IFNs and increased production of IL-1β following treatment of avian macrophage with resiquimod [15,27]. In agreement with the observations of these later studies, a lack of production of type IFNs have been shown in avian macrophages following stimulation of these cells with resiquimod [29].…”
Section: Discussionsupporting
confidence: 85%
“…In addition to CD8α+ T cell recruitment, macrophage recruitment has also been higher in the lungs following pre-hatch delivery of resiquimod. Previously, avian macrophages have been shown to elicit an antiviral response in vitro against avian influenza virus replication [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, resiquimod, a TLR7 ligand can increase IL-1β production in chicken macrophages, which leads to stimulation of antiviral responses against AIV. The induction of antiviral response against AIV by TLR7 ligands is attributable to IL-1β production and not to the NO production [66]. In addition, after treatment of embryonated chicken eggs with R848, a TLR7 ligand, IL-1β is upregulated in CAM, which may recruit macrophages to the CAM.…”
Section: Tlr7mentioning
confidence: 97%
“…In plasmacytoid dendritic cells (pDCs), after activation of TLR7 during IAV infection, IRF7 or nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) were activated via myeloid differentiation factor 88 (MyD88) to induce type I IFNs [132]. In avian macrophages, activation of TLR7 produced pro-inflammatory molecules such as interleukin (IL)-1β [133]. In addition, in mouse models, TLR7 played an important role in activation of NK cells [134].…”
Section: Activation Of Innate Immunity In Iav Infectionmentioning
confidence: 99%